Chinese Herb Astragalus membranaceus Enhances Recovery of Hemorrhagic Stroke: Double-Blind, Placebo-Controlled, Randomized Study. (12th March 2012) - Chen, Chun-Chung; Lee, Han-Chung; Chang, Ju-Hsin; Chen, Shuang-Shuang; Li, Tsai-Chung; Tsai, Chang-Hai; Cho, Der-Yang; Hsieh, Ching-Liang
Abstract : We tested the effect of Astragalus membranaceus (AM) on acute hemorrhagic stroke. Seventy-eight patients were randomly assigned to Group A (3 g of AM three times/day for 14 days); or Group B (3 g of placebo herb). A total of 68 patients (Group A 36, Group B 32) completed the trial. The increase of functional independence measure scale score between baseline and week 4 was 24.53 ± 23.40, and between baseline and week 12 was 34.69 ± 28.89, in the Group A was greater than 11.97 ± 11.48 and 23.94 ± 14.8 in the Group B (both P ≦ 0.05 ). The increase of Glasgow outcome scale score between baseline and week 12 was 0.75 ± 0.77 in the Group A was greater than 0.41 ± 0.50 in the Group B (P < 0.05 ). The results are preliminary and need a larger study to assess the efficacy of AM after stroke.